2018
DOI: 10.1007/s00406-018-0927-x
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar spectrum in major depressive disorders

Abstract: Growing evidence for the spectrum concept of most mental disorders, particularly mood disorders, has challenged the arbitrary distinctions inherent in the contemporary categorical diagnostic classification system. Detection of manic symptoms in the context of episodes of depression is particularly important because of the implications for differential treatment of bipolar vs unipolar depression. The purpose of this study is to characterize the magnitude and clinical correlates of subthreshold manic syndromes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…A number of reviews and guidelines have been published in this area, including burden of illness studies and studies of attitudes toward antipsychotic treatment [43,[66][67][68][69]78,82,90,96,97,107,[124][125][126]. Consequently, we did not undertake a formal systematic review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reviews and guidelines have been published in this area, including burden of illness studies and studies of attitudes toward antipsychotic treatment [43,[66][67][68][69]78,82,90,96,97,107,[124][125][126]. Consequently, we did not undertake a formal systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is an ongoing debate about the definition of hypomania [70] and concerns whether different rating scales for diagnosing (hypo)mania are interchangeable [76]. In practice, it can be difficult to differentiate between different BD disorders and other similar conditions, exacerbated by the presence of mixed states of BD, including depressive symptoms coexisting with manic symptoms [70,74,[77][78][79][80][81]. BD patients are typically sensitive to depressive symptoms but may not recognize their hypomanic or manic symptoms [69].…”
Section: Bipolar Disorders (Bd) Including Prevalence and Burden Of Ilmentioning
confidence: 99%
“…A growing body of evidence highlights both the epidemiologic and clinical relevance of the milder form of BD and PD. The application of the subthreshold bipolarity diagnostic criteria in a growing number of population surveys has shown that as many as 11.2% of adults presented bipolar spectrum disorders [58]. In addition to the epidemiological consistency of subthreshold BD, it is well known that this population is prone to experiencing severe role impairment and negative outcomes (including co-morbidity with Ads, high risks of physical illnesses, and suicidal attempts), which are virtually equivalent to those occurring in BD-I and BD-II [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…This can be seen in the current literature where results on comorbidity and co-symptomatology seem sometimes to predominate studies on disorders without comorbid conditions [2][3][4][5][6][7]. However, depending on the design of the studies, it is not always clear whether e.g.…”
mentioning
confidence: 99%